Cranial air embolism after transthoracic lung biopsy: A case report of a rare complication - Bulut, Hacı Taner; Soysaldı, Hasan; Çoraplı, Mahmut (Journal of Surgery and Medicine, 2022)
Cerebral air embolism is a rare and fatal complication of computed tomography-guided transthoracic lung biopsy. Lesions with pulmonary vein involvement—especially cavitary lesions—require particular care during procedures performed with a guided needle. Only 2 ml of an air embolism reaching the cerebral arteries is fatal, and a 1-ml cardiac air embolism can be fatal. Hyperbaric oxygen therapy should be started immediately to reduce mortality and ensure recovery among patients who develop unconsciousness and extremity paralysis during or after the procedure including when diagnosed with cranial CT imaging. Hyperbaric oxygen therapy has been reported to reduce mortality by up to 7% and reduces neurological deficits after 48 hours—even in delayed cases. Thus, transthoracic lung biopsy is important for the diagnosis of peripheral lung masses. Here, we present a rare complication after this procedure. Our goal here was to contribute to early diagnosis and treatment by creating awareness.